Agricultural All-Terrain Vehicle Safety: Hazard Control Methods Using the Haddon Matrix. Issue 4 (2nd October 2021) - Khorsandi, Farzaneh; Ayers, Paul; Denning, Gerene; Jennissen, Charles; Jepsen, Dee; Myers, Melvin; Oesch, Stephen; Pate, Michael; White, David J.
ABSTRACT: All-terrain vehicle (ATV) crashes are one of the leading causes of death and injury in agriculture across the United States. Use of ATVs is highly prevalent in rural areas and has seen an increase in their application for a variety of agricultural work tasks. Empirical research on the use of these vehicles for agricultural tasks and associated injuries is limited, especially in the United States. Moreover, little is known about the risk factors associated with ATV-related injuries while doing farm work. A comprehensive review was conducted to evaluate the current injury burden of ATV use in agriculture, the need for future research, and possible solutions related to agricultural ATV safety. Potential injury prevention approaches are evaluated based on the hierarchy of control, including elimination or substitution (using side-by-side vehicles instead of ATVs or modifying ATV design), engineering control (operator protection devices), administrative authority (regulations and standards in the United States and around the world), training, and use of personal protective equipment. In addition, vehicle nomenclature, risk factors, and crash mechanisms are reviewed. Recommendations to decrease the likelihood of ATV crashes and injuries are provided.